Current Anti-Inflammatory Therapies and the Potential of Secretory Phospholipase A2 Inhibitors in the Design of New Anti-Inflammatory Drugs: A Review of 2012 - 2018 - Sales, Thais A.; Marcussi, Silvana; Ramalho, Teodorico C. (Current Medicinal Chemistry, 2020)
The inflammatory process is a natural self-defense response of the organism to damage agents and its action mechanism involves a series of complex reactions. However, in some cases, this process can become chronic, causing much harm to the body. Therefore, over the years, many anti-inflammatory drugs have been developed aiming to decrease the concentrations of inflammatory mediators in the organism, which is a way of controlling these abnormal chain reactions. The main target of conventional anti-inflammatory drugs is the cyclooxygenase (COX) enzyme, but its use implies several side effects. Thus, based on these limitations, many studies have been performed, aiming to create new drugs, with new action mechanisms. In this sense, the phospholipase A2 (PLA2) enzymes stand out. Among all the existing isoforms, secretory PLA2 is the major target for inhibitor development, since many studies have proven that this enzyme participates in various inflammatory conditions, such as cancer, Alzheimer and arthritis. Finally, for the purpose of developing anti-inflammatory drugs that are sPLA2 inhibitors, many molecules have been designed. Accordingly, this work presents an overview of inflammatory processes and mediators, the current available anti-inflammatory drugs, and it briefly covers the PLA2 enzymes, as well as the diverse structural array of the newest sPLA2 inhibitors as a possible target for the production of new anti-inflammatory drugs.
Keywords: newest patents